Association Between Helicobacter pylori-Negative Peptic Ulcer Disease and Chronic Urticaria: A Retrospective Observational Study - Zhang C; Wei Y (Dove Medical Press, 2021)
Chengguo Zhang,1 Yinbin Wei2 1Department of Dermatology, Hanchuan People's Hospital, Hanchuan, 431600, People's Republic of China; 2Department of Infectious Diseases, Hanchuan People's Hospital, Hanchuan, 431600, People's Republic of ChinaCorrespondence: Yinbin WeiDepartment of Infectious Diseases, Hanchuan People's Hospital, No. 1 Renmin Avenue, Hanchuan, 431600, People's Republic of ChinaEmail weiyinbin1183840@163.comObjective: The association between peptic ulcer disease (PUD) and chronic urticaria (CU) is rarely examined in individuals without Helicobacter pylori infection. The study aimed to investigate the association between Helicobacter pylori-negative PUD and CU.Methods: Patients without Helicobacter pylori infection were retrospectively enrolled from those who visited the clinic or were admitted to the ward of the dermatological department with recent gastroscopy and Helicobacter pylori testing in a tertiary hospital between 2015 and 2019. After categorizing them as patients with and without PUD, we used propensity score matching to identify a cohort of PUD and a control cohort at a ratio of 1:2. CU was determined by examining medical records of the two cohorts, and logistic regression analyses were used to evaluate the association between PUD and CU with or without adjusting for covariates.Results: We included 40 patients with PUD as the PUD cohort and 80 patients without PUD as the control cohort, between which there were no significant differences in patient characteristics, including age, sex, and several comorbidities (P all > 0.05). Among the PUD cohort, 25.00% (10/40) of them were with CU, which was significantly higher than that in the control cohort 8.75% (7/80, P = 0.016). Results of logistic regression analyses showed PUD was significantly associated with increased risk of CU (odds ratio (OR) 3.48, 95% confidence interval (CI) 1.21- 9.99, P = 0.021), which was consistent with that after adjusted for potential confounding factors (OR 3.77, 95% CI 1.24- 11.45, P = 0.019).Conclusion: Helicobacter pylori-negative PUD is associated with increased risk of CU.Keywords: chronic urticaria, peptic ulcer, risk factors, Helicobacter pylori